Economic and Social Development of the Southern and Eastern Mediterranean Countries - Ayadi, Rym (Springer, 2015)
This book contains a unique collection of studies on key economic and social policy challenges faced by countries of the Southern and Eastern Mediterranean region in a short- and long-term perspective. Prepared within the EU funded FP7 project on „Prospective Analysis for the Mediterranean Region (MEDPRO)” conducted in 2010-2013 it takes account on recent political developments in the region (Arab Spring) and their potential consequences. It covers a broad spectrum of topics such as factors of economic growth, macroeconomic and fiscal stability, trade and investment, Euro-Mediterranean and intra-regional economic integration, private sector development and privatizations, infrastructure, tourism, agriculture, financial sector development, poverty and inequality, education, labor market and gender issues.